PROF. DR. ‘AISHAH ‘ABDURRAHMAN BINT AL-SHÂŢI’ : MUFASSIR WANITA ZAMAN KONTEMPORER - Fatimah Thohari (Dirosat : Journal of Islamic Studies, 2016)
Prof. Dr. ‘Aishah ‘Abdurrahman was more known by Bint al-Shati. She was the first woman interpreter in islamic world who lived in contemporary era—for the moment, she could be called the only one woman interpreter from the last generation of islamic reformer in Egypt—by publishing Magnum Opus that called by at-Tafsir al-Bayani li al-Qur’an al-Karim. Time after time, Bint Shati was coronated as an expert of moral/ethics by some institutions; Egypt government (1978), Kuwait government (1988), and The King Faishal (1994). She was a special woman figure, and she was productive in writing. There are about 40 titles which was written by her, especially in Qur’an.